2012
DOI: 10.1111/j.1526-4610.2012.02279.x
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐Month Analysis of Disability, Quality of Life, and Disease Course in Patients With Migraine

Abstract: In this study, migraine frequency and intensity were almost stable over 3 months, and an evident trend toward improvement was found in disability and in some health-related quality of life aspects, particularly in the social activity domain. Our results clearly indicate that continuity of care has a positive impact on patients' health status and functioning, also in stable patients already on anti-migraine therapy, and that the use of patient-oriented outcome measures is a viable way to capture such improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 71 publications
(79 reference statements)
3
16
1
Order By: Relevance
“…These positive outcomes were less evident in two studies: the double-blind, randomised placebo-controlled study on levetiracetam in CDH by Beran and Spira [6] and the randomized study on osteopathic manipulative treatment of female patients with migraine by Voigt et al [16], In these reports, however, some changes towards improvement in QoL and in disability were observed. Similar results were found in the two observational studies by Raggi et al [13,14] in which small changes in QoL and disability were detected over a three-month follow-up period in samples of patients currently under treatment, although headache frequency was substantially stable.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…These positive outcomes were less evident in two studies: the double-blind, randomised placebo-controlled study on levetiracetam in CDH by Beran and Spira [6] and the randomized study on osteopathic manipulative treatment of female patients with migraine by Voigt et al [16], In these reports, however, some changes towards improvement in QoL and in disability were observed. Similar results were found in the two observational studies by Raggi et al [13,14] in which small changes in QoL and disability were detected over a three-month follow-up period in samples of patients currently under treatment, although headache frequency was substantially stable.…”
Section: Resultssupporting
confidence: 76%
“…Four studies described a surgical approach: two were procedures for deactivation of trigger sites [9,10], one approach was the occipital nerve stimulation [11], and one approach was bariatric surgery for obese patients patients comorbid migraine [12]. Two studies reported short-term longitudinal observations of patients currently under treatment for migraine who were prescribed tailored medications including both acute and prophylactic ones [13,14]. Two studies presented results of non-pharmacological treatments, the first was based on a patient education programme [15] and the second on osteopathic manipulative treatment [16].…”
Section: Resultsmentioning
confidence: 99%
“…The sample of our study had considerably high disability and low QoL status: WHODAS 2.0 score was more than twofold that of the Italian normative value, and 46% higher than that observed in EM patients; MSQ scores were approximately 27‐36% lower than those observed by Cevoli and colleagues in a sample of 953 Italian migraineurs (2.5% with CM‐MO). Although the mean score at BDI‐2 was indicative of a mild depression level, more than a third of the patients had marked signs of mood reduction.…”
Section: Discussioncontrasting
confidence: 58%
“…A recent study reported that tension-type headache (TTH) and migraine were also the most common recurrent headaches with prevalences of 20.77% and 14.7%, respectively (Vos et al 2012). Headache compromises a person's quality of life and reduces their functional capability as well as their work capacity Raggi et al 2013). This results in high socioeconomic cost mainly due to days off work (Burton et al 2002;Pradalier et al 2004;Berg and Stovner 2005;Bloudek et al 2012;Lanteri-Minet 2014).…”
Section: Introductionmentioning
confidence: 99%